New Simple CMOS Realization of Voltage Differencing Transconductance Amplifier and Its RF Filter Application - Yesil, Abdullah; Kacar, Firat; Kuntman, Hakan (Společnost pro radioelektronické inženýrství, 2011)
The voltage differencing transconductance amplifier (VDTA) is a recently introduced active element for analog signal processing. However, the realization of VDTA is not given by any author yet. In this work, a new and simple CMOS realization of VDTA is presented. The proposed block has two voltage inputs and two kinds of current output, so it is functional for voltage- and transconductance-mode operation. Furthermore, VDTA exhibits two different values of transconductance so that there is no need to external resistors for VDTA based applications which seems to be a good advantage for analog circuit designer. A CMOS implementation of VDTA and a voltage-mode VDTA based filter are proposed and simulated. An application example of fourth order flat-band band-pass amplifier is given and the performance of the circuit is demonstrated by comparing the theory and simulation.
Keywords: Voltage differencing transconductance amplifier; voltage mode filter; CMOS integrated circuit